Evaluating Prehistoric Sea Ice Variability and Culture Change in Northwest Alaska. - Freeburg, Adam (Arctic Portal, 2011)
Young researcher Adam Freeburg, University of Washington, USA, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.